THE INITIAL RESULTS OF THE SUSPENDED SEDIMENT DYNAMICS DURING THE DRY SEASON IN THE HAU RIVER MOUTH AREA - Tien, Nguyen Ngoc; Uu, Dinh Van; Sao, Nguyen Tho; Cuong, Do Huy; Thanh, Nguyen Trung; Dang, Vu Hai; Thuc, Do Ngoc (Vietnam Journal of Marine Science and Technology, 2017)
During the dry season (April 2014 and March 2015), the program of cooperation in science and technology between Vietnam and the United States and the independent project VAST-DLT.06/15-16 have conducted two surveys aiming to investigate deposition and sptial and temporal distribution of suspended sediment concentration under the domination by hydrodynamic processes such as wave, current, river flow. In addition, we also investigated the effect of tidal current in relationship with concentration of suspended sediment. Three 12-hour continuous monitoring stations of suspended sediment factors, water level and current are located on the topset at a depth of 8 m, the foreset at a depth of 15 m and the bottomset at a depth of 25 m, with a distance between the two stations about 3 km. In which, the concentrations of suspended sediment (SSCs) in the range of particle sizes from 1.25 μm to 250 μm and particle diameter are measured by LISST-25x (Suspended Sediment Sensor), water level, velocity and current direction are measured by the ADCP. Results of data analysis show that the distributions of particle diameter of suspended sediment over time on the topset, the foreset and the bottomset are different and do not change much under tidal phases. Meanwhile, the concentrations of suspended sediment (SSCs) correlate with velocity and fluctuate under tidal phases. Suspended sediment is deposited at tidal transition and reactivates when current velocities increase in flood and ebb tide phases. The survey data show that the increase of current velocity during flood tide phase causes re-suspension of bottom sediments and increases the concentration of suspended sediment. At flood tide phase corresponding to strong velocity, suspended sediment moves faster and vice versa at ebb tide phase, smaller current velocity makes the movement speed of suspended sediment slow.